Effect of transportation on the performance and carcass traits of halothane sensitive pigs - Manju Sasidharan (Department of Livestock Production Management, College of Veterinary and Animal Sciences, 1997)
A study to assess the effect of transportation on the performance and carcass traits of halothane sensitive pigs was carried out. Twenty four weaner piglets were selected after screening for halothane sensitivity. Twelve piglets, six from halothane positive and six from halothane negative were transported. The halothane negative pigs showed more aggressive behaviour during transport, and the loss in body weight was significantly (P < 0.01) higher for the halothane negative pigs. A transportation for 150 km (Five hours) did not affect the further growth performance, average fortnightly gain and feed conversion efficiency. At 210 days of age the transported group was subjected to a second transportation of 150 km and were slaughtered and carcass characteristic were studied. Shrinkage was more for halothane negative group. The live weight at slaughter, carcass length dressing percentage, loin eye area, backfat thickness and organ weights did not show any significant difference. The meat pH was lower for halothane positive pigs and transported group indicative of pale soft exudative (PSE) condition. The crude fat content of liver and kidney did not differ between any of the groups. Packed cell volume and blood pH did not vary between the groups. Erythrocyte sedimentation rate was significantly (P < 0.05) higher for transported halothane positive group. There was no significant difference in serum lactate dehydrogenase content. But serum creatine phosphokinase was higher for halothane positive pigs and the values increased on transportation.